A Functional Variant on 9p21.3 Related to Glioma Risk Affects Enhancer Activity and Modulates Expression of CDKN2B‐AS1. Issue 10 (29th June 2021) - Ali, Mourad Wagdy; Patro, C. Pawan K.; Devall, Matthew; Dampier, Christopher H.; Plummer, Sarah J.; Kuscu, Cem; Adli, Mazhar; Lai, Rose K.; Casey, Graham
Abstract: Genome‐wide association studies have identified SNPs associated with glioma risk on 9p21.3, but biological mechanisms underlying this association are unknown. We tested the hypothesis that a functional SNP on 9p21.3 affects activity of an enhancer, causing altered expression of nearby genes. We considered all SNPs in linkage disequilibrium with the 9p21.3 sentinel SNP rs634537 that mapped to putative enhancers. An enhancer containing rs1537372 exhibited allele‐specific effects on luciferase activity. Deletion of this enhancer in GBM cell lines correlated with decreased expression of CDKN2B‐AS1 . Expression quantitative trait loci analysis using non‐diseased brain samples showed rs1537372 to be a consistently significant eQTL for CDKN2B‐AS1 . Additionally, our analysis of Hi‐C data generated in neural progenitor cells showed that the bait region containing rs1537372 interacted with the CDKN2B‐AS1 promoter. These data suggest rs1537372, a SNP at the 9p21.3 risk locus, is a functional variant that modulates expression of CDKN2B‐AS1 .